Supplementation of Silkworm Pupae Meal on Productivity and Quality of Lohmann Brown Chicken Eggs - Winarno, Winarno; Fuah, Asnath Maria; Endrawati, Yuni Cahya; Ulfah, Maria (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
Protein is known as the most expensive nutritional component of chicken feed, reaching 15% of the cost of feed, compared to other components. Silkworm pupae are an industrial waste of silk yarn spinning which has the potential as poultry feed with the advantage of containing 48%-60% crude protein and 18 amino acids. The purpose of this study was to determine the effect of Bombyx mori silkworm pupae supplementation on the productivity and physical quality of Lohmann Brown laying hens aged 60-72 weeks. The research material was B. mori silkworm pupae meal mixed in the ration. The research method used a completely randomized design (CRD) with 3 treatments, namely P0 (ration + 0% silkworm pupae meal), P1 (ration + 3% silkworm pupae meal) and P3 (ration + 6% silkworm pupae meal). Each treatment consisted of 5 replications with 3 chickens in each replication. The variables observed included the productivity and physical quality of laying hens. The results showed that the addition of silkworm pupae meal by 6% in the ration significantly increased (P<0.5) egg production, feed consumption, feed conversion and egg quality, especially shell weight (g).